(untitled) (Mustansiria Dental Journal, 2019)
The aim of our study was to analyze the stress and anxiety in patients undergoing routine denture insertion, by the assessment of cortisol in saliva, which can be considered as one of the major hormones that is released during stressful events. Stress is defined as an organism’s total response to an environmental condition or stimulus, also known as a stressor. Cortisol is a stress hormone produced by the adrenal glands. It is one of the stress hormones, and is produced at higher levels in individuals who are prone to stress. Aside from contributing factors such as work and emotions, it is also produced at greater levels by people who work early morning shifts. After obtaining the ethical approval and the patients were consented for their role in this study, we examined 22 patients (8 males, and 14 females).The age ranged from 22-74 with mean age of 59.6 & 42.6. I collected two salivary samples from each patient using spitting methods; one hour pre and one hour post insertion of removable partial and complete dentures (R.P.D. & R.C.D.). The samples were assessed and analyzed using ELISA test. Statistical analysis was performed using SPSS statistical software (version 19).ANOVA and t-test was applied to obtain the significance and correlation between the examined samples. Statically significant association regarding the difference of mean (post and pre using of denture) of cortisol level regarding the gender of the patients, where the difference of mean of female was higher than that of male patients (0.2, 0.14) respectively, p =0.001.My study revealed that salivary cortisol is within its highest levels after insertion of R.P.D. & R.C.D. in one hour. Significant association regarding the age was reported and the R.C.D group has had higher mean than that of R.P.D group.